Proceedings of the 15th European Conference on Cognitive Ergonomics: The Ergonomics of Cool Interaction 2008
DOI: 10.1145/1473018.1473065
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the digital divide for deaf signer users

Abstract: Motivation -In order to design strategies to overcome deaf signer users' digital divide, the authors portray an overview of some of the cognitive processing characteristics of this type of users during Web information search based on insights gained from the Cogniweb project's empirical research. Research approach -Critical review of 5 experiments on Web Information Search which manipulated system and users' variables. Findings/Design -The results highlight the relevance of 3 cognitive factors as predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Also there are some works regarding how deaf people use Information and Communication Technologies (ICTs) (e.g. [10], [12] and [15]) However, to the the best of our knowledge, an investigation aimed at characterizing interaction among members of deaf communities on social networks has not yet been published.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Also there are some works regarding how deaf people use Information and Communication Technologies (ICTs) (e.g. [10], [12] and [15]) However, to the the best of our knowledge, an investigation aimed at characterizing interaction among members of deaf communities on social networks has not yet been published.…”
Section: Related Workmentioning
confidence: 99%
“…Works like [10] and [12] found that, as listeners, the deaf also want to communicate with a variety of people and quickly, but what differs is the language used in this interaction. Authors in [15] describe the important role of ICTs in the autonomy and socialization of the deaf, and note that not all the specific characteristics of these users have been considered in the interaction models of these systems.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations